The Parenting Self-Efficacy Of Mothers Of Children With Moderate Intellectual Disability In Terms Of Hardiness - Salsabila, Mustamira Sofa; Fitriani, Annisa; Amelia, Amelia (ANFUSINA: Journal of Psychology, 2024)
Parenting a child with an intellectual disability is a difficult challenge for a mother, who must have confidence and resilience to care for and raise a child as a mandate from Allah. This study aims to examine parenting self-efficacy in mothers of children with intellectual disabilities in terms of hardiness. Parenting self-efficacy refers to the perceived ability of parents to positively impact their children's behavior and development. Hardiness is a personality trait that allows people to survive difficult situations (Kobasa, Maddi & Kahn, 1982). This study employed the purposive sampling technique with 57 mothers with intellectually disabled children. The instruments to collect the self-efficacy data were the parenting task index (SEPTI) and the toughness scale. The data was analyzed using the Pearson product-moment correlation formula assisted by JASP 18.1 software for Windows. The study found a significant positive correlation between hardiness and parenting self-efficacy among mothers of intellectually disabled children (R = 0.539 and R² = 0.291, p < 0.01). Thus, parenting self-efficacy effectively contributed 29.1%, with the remaining 70.9% influenced by variables not investigated in this study. Keywords: Hardiness, parenting self-efficacy, mothers of children with intellectual disability.